Peran Pola Pengasuhan Orangtua Terhadap Kepuasan Hidup Dan Sikap Nasionalisme Pada Remaja - R. Rahaditya; Agoes Dariyo (Journal An-Nafs: Kajian Penelitian Psikologi, 2018)
Nationalism as a love of the homeland, or attitude to love the nation and its own country. Nationalism must be developed from the beginning through the role of parenting parenting of children in the family. In addition, nationalism also grows in the life of adolescents who have life satisfaction. On the other hand, parenting also plays an important role in meeting the satisfaction of the lives of teenagers in the family. This research intends to know the role of parenting to the satisfaction of life and the attitude of teen nationalism. Data collection with the questionnaire is parenting parenting, life satisfaction and nationalism. Retrieved data of 220 adolescents. Analytical technique using anova and regression. The results of this study can be summarized as follows: there is no difference in nationalism attitude in terms of parental parenting; there are differences in life satisfaction in terms of parental parenting, and there is a role of life satisfaction with the attitude of nationalism in adolescents. Furthermore, the results can be seen in the discussion